Multi-layer co-extrusion two-way stretch film and preparation method and application thereof
Through the multi-layer coextrusion bidirectional stretch film technology, the AB structure of the high-extension PET and PP layers is used to solve the problems of adhesive contamination and poor performance in the production process of traditional PET composite films, and the food packaging film without adhesive is realized Production has good mechanical properties and environmental protection advantages.
Patent Information
- Application Number
- CN202310718864.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-16
AI Technical Summary
The PET composite film used in traditional food packaging requires adhesives during the production process, which leads to environmental pollution and poor material performance, making it difficult to form a film by melting and co-extruding.
Using multi-layer coextrusion bidirectional stretch film technology, the high-extension PET layer and PP layer are produced by direct esterification-melting polycondensation method, and melt extrusion is performed using a series screw extruder and coextrusion die head, combining longitudinal and transverse stretching. The film with AB structure was formed.
The film production without adhesive process is achieved, with good physical and mechanical properties, reducing costs and environmental pollution, suitable for food packaging, and avoiding the problem of poor performance of PET and PP materials.
Smart Images

Figure BDA0004290427230000141 
Figure BDA0004290427230000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a multi-layer co-extruded biaxially stretched film and a preparation method and application thereof. Background Art
[0002] Among plastic flexible packaging materials, food packaging is its largest application market. With the improvement of consumption level, the requirements for food packaging are becoming more and more stringent, which has prompted the development of high-barrier multifunctional packaging film materials. In a general sense, the structure of packaging film products depends on the functional requirements of the packaging for the film. For food packaging, packaging materials generally need to have good oxygen and water vapor barrier capabilities, good heat sealing properties, certain sterilization and heat resistance, strong mechanical properties, good printing properties and optical properties. PET polyester is often used as one of the materials for multi-layer composite films due to its excellent comprehensive properties.
[0003] Traditional PET composite films for food packaging commonly use structures such as PET / VMPET / LLDPE or PET / VMCPP. It is necessary to prepare a raw material film separately and then bond it with an adhesive. The volatilization of adhesives and solvents used in the production process of the multi-layer composite film can easily cause environmental pollution.
[0004] When preparing films by multi-layer co-extrusion, the multi-layer films are extruded in one time, which is simple in process, energy-saving, high in production efficiency, low in cost, environmentally friendly, avoids the use of adhesives between layers, does not have the problem of residual solvents, and has no odor, making it suitable for food and medical device packaging. However, there is a large gap between PET polyester and polyolefin materials such as PP in terms of melting point, stretch ratio and other properties, making it difficult to form films in one time through melt co-extrusion. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a multi-layer co-extruded biaxially oriented film and a preparation method and application thereof, wherein two layers of PET and PP are co-extruded and biaxially oriented to form a film.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A multi-layer co-extruded biaxially oriented film has an AB structure, wherein the A layer is a high-extensibility PET layer and the B layer is a PP layer. The elongation at break MD of the material is 170-200%, and TD is 68-80%; the tensile strength MD is 220-280 MPa, and TD is 300-330 MPa.
[0008] In the technical solution of the present invention: the melting point of the high-ductility PET copolyester is between 177-231°C; the maximum transverse stretching ratio of the high-ductility PET copolyester is 7.2-8.6 times (test conditions: the copolyester slices are dried and extruded into 150 μm thick slices, which are placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature of 140°C and preheating time of 20s).
[0009] In the technical solution of the present invention: the high-ductility PET is produced by using terephthalic acid, isophthalic acid, polyethylene glycol ester of aliphatic dibasic acid and ethylene glycol as raw materials, and adopts a direct esterification-melt polycondensation method to produce the polyester raw material.
[0010] In some preferred technical schemes: the total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, the total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, and the mass ratio of terephthalic acid, isophthalic acid, and polyaliphatic dibasic acid ethylene glycol ester is 80-85:5-15:5-15.
[0011] In some preferred technical solutions: the molar ratio of the diol to the dibasic acid is 1-1.5:1, the diol is ethylene glycol, and the dibasic acid is terephthalic acid and isophthalic acid.
[0012] In some preferred technical schemes: the poly(ethylene glycol) of aliphatic dibasic acid can be one or more of poly(ethylene glycol) malonate (PEP), poly(ethylene glycol) succinate (PEB), poly(ethylene glycol) glutarate (PEG), poly(ethylene glycol) adipate (PEA), poly(ethylene glycol) suberate (PES), etc.
[0013] In the technical solution of the present invention, the thickness ratio of the PET layer of layer A to the PP layer of layer B is 1-10:1-10.
[0014] In the technical solution of the present invention: the catalyst used in the direct esterification-melt polycondensation method is ethylene glycol antimony, the antimony atoms account for 100-300 ppm of the total polyester mass, the temperature of the esterification reaction is 250-260°C, the temperature of the polycondensation reaction is 280-285°C, and the pressure of the polycondensation reaction is below 100 Pa absolute pressure.
[0015] A method for preparing the above-mentioned multi-layer co-extruded biaxially stretched film, wherein layer A and layer B are melt-extruded by a tandem screw extruder, and the two layers of raw materials are electrostatically attached to a cold drum through a co-extrusion die head equipped with a co-extrusion adapter to form a cast sheet; the thick sheet obtained after extrusion is sequentially stretched longitudinally by 3-5 times, stretched transversely by 6-8 times, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 20 to 30 μm.
[0016] In the technical solution of the present invention: Layer A is a high-extensibility PET layer, which has a processing temperature similar to that of BOPP and serves as an outer layer printing. Layer B is a PP layer, which serves as a heat seal.
[0017] After the multi-layer co-extruded biaxially oriented film is prepared, the BOPP layer can be aluminum-plated to give the film a certain barrier property to meet the requirements of food packaging.
[0018] Unconventional testing methods:
[0019] The maximum stretching ratio of the high-ductility PET is evaluated by a tensile testing machine. The copolyester slice is dried and extruded into a 150 μm thick slice, which is placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slice are a preheating temperature of 140° C. and a preheating time of 20 seconds. The maximum ratio of the longitudinal stretching of 4.0 times and the transverse stretching without breaking the film is the transverse maximum stretching ratio.
[0020] The film-forming property of the multi-layer co-extruded biaxially oriented film is evaluated by a tensile testing machine. The continuous thick sheet obtained by multi-layer co-extrusion is cut into a 10cm×10cm thick sheet, preheated at a preheating temperature of 140°C for 20s by a tensile testing machine, then stretched 4.0 times in the longitudinal direction and 7.0 times in the transverse direction, and then fixed at 190°C for 3s. No film breakage in 10 biaxial stretching tests indicates that the product has excellent film-forming property, which is indicated by ○; film breakage less than or equal to 3 times indicates that the product has good film-forming property, which is indicated by △; film breakage greater than 3 times or failure to form a film indicates that the product has poor film-forming property, which is indicated by ×.
[0021] Effects of the Invention
[0022] The present invention obtains a PET / PP multi-layer co-extruded biaxially stretched film, which has good film-forming properties, good physical and mechanical properties, reaches the national standard of BOPP, does not involve a traditional gluing process, reduces the use of adhesives, reduces costs, and is beneficial to safety and health as well as environmental protection.
[0023] In the technical scheme of the present invention: PTA is terephthalic acid, IPA is isophthalic acid, PEA is polyethylene adipate, PEB is polyethylene succinate, and PEG is polyethylene glutarate. DETAILED DESCRIPTION
[0024] The present invention is further described below in conjunction with embodiments, but the protection scope of the present invention is not limited thereto:
[0025] Example 1
[0026] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 80%, isophthalic acid accounts for 10%, and polyethylene adipate (PEA) accounts for 10%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 190°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140° C., preheating time of 20 s, and maximum transverse stretching ratio of 8.0.
[0027] The B layer of the product is the PP layer.
[0028] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1 (mass ratio). The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0029] The co-extruded film has excellent film-forming properties, with a longitudinal elongation at break of 200% and a tensile strength of 220 MPa; a transverse elongation at break of 80% and a tensile strength of 300 MPa.
[0030] Example 2
[0031] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 85%, isophthalic acid accounts for 5%, and polyethylene adipate accounts for 10%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 225°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140°C, preheating time of 20 seconds, and maximum transverse stretching ratio of 7.2.
[0032] The B layer of the product is the PP layer.
[0033] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0034] The co-extruded film has good film-forming properties, with a longitudinal elongation at break of 170% and a tensile strength of 280 MPa; a transverse elongation at break of 68% and a tensile strength of 324 MPa.
[0035] Example 3
[0036] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 80%, isophthalic acid accounts for 5%, and polyethylene adipate accounts for 15%. The catalyst is ethylene glycol antimony, in which antimony atoms account for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 185°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 8.0.
[0037] The B layer of the product is the PP layer.
[0038] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0039] The co-extruded film has excellent film-forming properties, with a longitudinal elongation at break of 195% and a tensile strength of 225 MPa; a transverse elongation at break of 78% and a tensile strength of 3`0 MPa.
[0040] Example 4
[0041] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 85%, isophthalic acid accounts for 10%, and polyethylene adipate accounts for 5%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 225°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140°C, preheating time of 20 s, and maximum transverse stretching ratio of 7.4.
[0042] The B layer of the product is the PP layer.
[0043] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0044] The co-extruded film has good film-forming properties, with a longitudinal elongation at break of 177% and a tensile strength of 268 MPa; a transverse elongation at break of 70% and a tensile strength of 330 MPa.
[0045] Example 5
[0046] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 80%, isophthalic acid accounts for 15%, and polyethylene adipate accounts for 5%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 188°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140° C., preheating time of 20 s, and maximum transverse stretching ratio of 8.0.
[0047] The B layer of the product is the PP layer.
[0048] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick sheet is stretched 4 times in the longitudinal direction and 7 times in the transverse direction, and then heat-set, relaxed, pulled, and rolled. The co-extruded film has good film-forming properties, with a longitudinal elongation of 197% and a tensile strength of 223MPa; a transverse elongation of 80% and a tensile strength of 305MPa.
[0049] Example 6
[0050] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 80%, isophthalic acid accounts for 10%, and polyethylene succinate (PEB) accounts for 10%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 195°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140° C., preheating time of 20 s, and maximum transverse stretching ratio of 8.0.
[0051] The B layer of the product is the PP layer.
[0052] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0053] The co-extruded film has excellent film-forming properties, with a longitudinal elongation at break of 197% and a tensile strength of 228 MPa; a transverse elongation at break of 78% and a tensile strength of 310 MPa.
[0054] Example 7
[0055] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 80%, isophthalic acid accounts for 10%, and polyethylene glycol glutarate (PEG) accounts for 10%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 193°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140° C., preheating time of 20 s, and maximum transverse stretching ratio of 8.0.
[0056] The B layer of the product is the PP layer.
[0057] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0058] The co-extruded film has excellent film-forming properties, with a longitudinal elongation at break of 198% and a tensile strength of 226 MPa; a transverse elongation at break of 79% and a tensile strength of 305 MPa.
[0059] Reference example 1
[0060] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 75%, isophthalic acid accounts for 10%, and polyethylene adipate accounts for 15%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 177°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140°C, preheating time of 20 seconds, and maximum transverse stretching ratio of 8.6.
[0061] The B layer of the product is the PP layer.
[0062] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0063] The co-extruded film has good film-forming properties, with a longitudinal elongation at break of 230% and a tensile strength of 186 MPa; a transverse elongation at break of 87% and a tensile strength of 281 MPa.
[0064] Reference example 2
[0065] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 75%, isophthalic acid accounts for 15%, and polyethylene adipate accounts for 10%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and the Tm is 180°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140° C., preheating time of 20 s, and maximum transverse stretching ratio of 8.1.
[0066] The B layer of the product is the PP layer.
[0067] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0068] The co-extruded film has good film-forming properties, with a longitudinal elongation at break of 220% and a tensile strength of 180 MPa; a transverse elongation at break of 90% and a tensile strength of 270 MPa.
[0069] Reference example 3
[0070] The product A layer is commercially available PET polyester, the intrinsic viscosity of the copolyester is 0.645dL / g, and Tm is 250℃. The copolyester slices are dried and extruded into 150μm thick slices, which are placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140℃, preheating time 20s, and the maximum transverse stretching ratio is 4.4.
[0071] The B layer of the product is the PP layer.
[0072] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0073] Reference example 4
[0074] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 95%, and polyethylene adipate accounts for 5%. The molar ratio of ethylene glycol to terephthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained after extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.70dL / g, and Tm is 236°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 5.0.
[0075] The B layer of the product is the PP layer.
[0076] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0077] Reference example 5
[0078] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 90%, and polyethylene adipate accounts for 10%. The molar ratio of ethylene glycol to terephthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained by extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and the Tm is 213°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 6.4.
[0079] The B layer of the product is the PP layer.
[0080] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0081] Reference example 6
[0082] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 85%, and polyethylene adipate accounts for 15%. The molar ratio of ethylene glycol to terephthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained after extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 209°C. The copolyester slices are dried and extruded into 150μm thick slices. After one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 7.2.
[0083] The B layer of the product is the PP layer.
[0084] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0085] Reference example 7
[0086] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 80%, and polyethylene adipate accounts for 20%. The molar ratio of ethylene glycol to terephthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained after extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 186°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 8.5.
[0087] The B layer of the product is the PP layer.
[0088] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0089] The co-extruded film has excellent film-forming properties, with a longitudinal elongation at break of 220% and a tensile strength of 176 MPa; a transverse elongation at break of 102% and a tensile strength of 246 MPa.
[0090] Reference example 8
[0091] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and isophthalic acid in the raw materials is 100%, terephthalic acid accounts for 95%, and isophthalic acid accounts for 5%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained by extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.7dL / g, and Tm is 240°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 4.7.
[0092] The B layer of the product is the PP layer.
[0093] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0094] Reference example 9
[0095] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and isophthalic acid in the raw materials is 100%, terephthalic acid accounts for 90%, and isophthalic acid accounts for 10%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained after extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 231°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 5.4.
[0096] The B layer of the product is the PP layer.
[0097] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0098] Reference example 10
[0099] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and isophthalic acid in the raw materials is 100%, terephthalic acid accounts for 85%, and isophthalic acid accounts for 15%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained by extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 210°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 6.2.
[0100] The B layer of the product is the PP layer.
[0101] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0102] Reference example 11
[0103] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid and isophthalic acid in the raw materials is 100%, terephthalic acid accounts for 80%, and isophthalic acid accounts for 20%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester slices are obtained after extrusion, drawing, pelletizing and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 192°C. The copolyester slices are dried and extruded into 150μm thick slices. After being placed for one day, they are uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slices are preheating temperature 140°C, preheating time 20s, and the maximum transverse stretching ratio is 7.0.
[0104] The B layer of the product is the PP layer.
[0105] Layer A and layer B are melt extruded through a tandem screw extruder, and the co-extrusion ratio is 1:1. The extrusion temperature is 280℃, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film is stretched 4 times in the longitudinal direction, 7 times in the transverse direction, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 25μm. The A layer is 12μm and the B layer is 13μm.
[0106] The co-extruded film has good film-forming properties, with a longitudinal elongation at break of 215% and a tensile strength of 180 MPa; a transverse elongation at break of 100% and a tensile strength of 250 MPa.
[0107] Reference example 12
[0108] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 90%, isophthalic acid accounts for 5%, and polyethylene adipate accounts for 5%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm is 220°C. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140° C., preheating time of 20 s, and maximum transverse stretching ratio of 8.0.
[0109] The B layer of the product is the PP layer.
[0110] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0111] Reference example 13
[0112] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 75%, isophthalic acid accounts for 5%, and polyethylene adipate accounts for 20%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm disappears. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140°C, preheating time of 20 seconds, and maximum transverse stretching ratio of 8.8.
[0113] The B layer of the product is the PP layer.
[0114] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0115] Reference example 14
[0116] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 70%, isophthalic acid accounts for 15%, and polyethylene adipate accounts for 15%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm disappears. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140° C., preheating time of 20 s, and maximum transverse stretching ratio of 9.1.
[0117] The B layer of the product is the PP layer.
[0118] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0119] Reference example 15
[0120] The product A layer is a high-extensibility PET copolyester. The total mass of terephthalic acid, isophthalic acid, and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, terephthalic acid accounts for 75%, isophthalic acid accounts for 20%, and polyethylene adipate accounts for 5%. The molar ratio of ethylene glycol to the total of terephthalic acid and isophthalic acid is 1.2. The catalyst is ethylene glycol antimony, in which the antimony atom accounts for 200ppm of the total polyester mass. The conventional esterification reaction is carried out at 256°C by direct esterification-melt polycondensation method. After the esterification is completed, the polycondensation reaction is carried out at 283°C and the absolute pressure is below 100Pa. After the reaction is completed, the copolyester chips are obtained after extrusion, drawing, pelletizing, and drying. The intrinsic viscosity of the copolyester is 0.79dL / g, and Tm disappears. The copolyester chips were dried and extruded into 150 μm thick sheets, which were placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick sheets were preheating temperature of 140°C, preheating time of 20 seconds, and maximum transverse stretching ratio of 8.6.
[0121] The B layer of the product is the PP layer.
[0122] Layer A and layer B are melt extruded through a tandem screw extruder, with a co-extrusion ratio of 1:1. The extrusion temperature is 280°C, and the two layers of raw materials are electrostatically attached to the cold drum through a co-extrusion die head equipped with a co-extrusion adapter. The thick film breaks during biaxial stretching and cannot be formed into a film.
[0123] Performance test standards:
[0124] The maximum stretching ratio of the high-ductility PET is evaluated by a tensile testing machine. The copolyester slice is dried and extruded into a 150 μm thick slice, which is placed for one day and then uniaxially stretched on a tensile testing machine. The stretching conditions of the thick slice are a preheating temperature of 140° C. and a preheating time of 20 seconds. The maximum ratio of the longitudinal stretching of 4.0 times and the transverse stretching without breaking the film is the transverse maximum stretching ratio.
[0125] The film-forming property of the multi-layer co-extruded biaxially oriented film is evaluated by a tensile testing machine. The continuous thick sheet obtained by multi-layer co-extrusion is cut into a 10cm×10cm thick sheet, preheated at a preheating temperature of 140°C for 20s by a tensile testing machine, then stretched 4.0 times in the longitudinal direction and 7.0 times in the transverse direction, and then fixed at 190°C for 3s. No film breakage in 10 biaxial stretching tests indicates that the product has excellent film-forming property, which is indicated by ○; film breakage less than or equal to 3 times indicates that the product has good film-forming property, which is indicated by △; film breakage greater than 3 times or failure to form a film indicates that the product has poor film-forming property, which is indicated by ×.
[0126] The elongation at break and tensile strength are tested according to the national standard GB / T 1040.1-2018 “Determination of tensile properties of plastics”.
[0127]
[0128]
[0129] The test results of the embodiments of the present invention and the reference examples are listed in Table 1. The present invention utilizes modified PET polyester and PP for coextrusion stretching to obtain a double-layer biaxially stretched film product with good film-forming property, which can be used in the field of packaging to reduce processes, achieve energy saving and consumption reduction, reduce costs, reduce organic reagent pollution and other problems. The PET component is modified by two monomers in situ copolymerization to achieve the purpose of coextrusion stretching with PP. The poly(aliphatic dibasic acid glycol) monomer used is a long straight chain structure, similar to the PP structure, which improves the compatibility with PP materials, solves the problems of poor compatibility between PET and PP materials, poor film-forming property of prepared films and low mechanical properties, and its polyester structure also plays a role in improving the thermal stability of the overall material; the IPA monomer used is a polar aromatic structure, which plays a role in lowering the melting point while maintaining the softening point of the PET material, reducing the difficulty of coextrusion processing of PET and PP, and at the same time does not reduce the mechanical properties of PET itself. Compared with reference examples 1, 2, 13, 14, and 15, the mechanical strength of the film is affected when the reference examples exceed the scope of the present invention, as shown by an increase of more than 80% in elongation at break, a decrease in tensile strength of less than 200 MPa in MD, and less than 300 MPa in TD, and a significant decrease in mechanical properties. Compared with reference examples 3, 4, 5, 6, 8, 9, and 10, the film-forming property is poor and difficult to form a film when the reference examples are lower than the scope of the present invention. Compared with reference examples 7 and 11, when only one of isophthalic acid or poly(ethylene glycol) dicarboxylic acid is used as the modified component, the mechanical properties of the film are significantly reduced.
Claims
1. A multi-layer co-extruded biaxially oriented film, Features: The biaxially oriented film has an AB structure, wherein the A layer is a high-extensibility PET layer and the B layer is a PP layer. The elongation at break of the material is 170-200% in MD and 68-80% in TD; the tensile strength is 220-280 MPa in MD and 300-330 MPa in TD.
2. The multi-layer co-extruded biaxially oriented film according to claim 1, Features: The melting point of the high-ductility PET copolyester is between 177-231°C.
3. The multi-layer co-extruded biaxially oriented film according to claim 1, Features: The maximum transverse stretching ratio of the high-extensibility PET copolyester is 7.2-8.6 times.
4. The multi-layer co-extruded biaxially oriented film according to claim 1, Features: The high-ductility PET is made of terephthalic acid, isophthalic acid, polyethylene glycol ester of aliphatic dibasic acid and ethylene glycol, and is produced by a direct esterification-melt polycondensation method.
5. The multi-layer co-extruded biaxially oriented film according to claim 4, Features: The total mass of terephthalic acid, isophthalic acid and aliphatic dibasic acid ethylene glycol ester in the raw materials is 100%, and the mass ratio of terephthalic acid, isophthalic acid and poly(aliphatic dibasic acid ethylene glycol ester) is 80-85:5-15:5-15.
6. The multi-layer co-extruded biaxially oriented film according to claim 4, Features: The molar ratio of the diol to the dibasic acid is 1-1.5:1, the diol is ethylene glycol, and the dibasic acid is terephthalic acid and isophthalic acid.
7. The multi-layer co-extruded biaxially oriented film according to claim 4, Features: The poly(ethylene glycol) ester of aliphatic dibasic acid may be one or more of poly(ethylene glycol) malonate, poly(ethylene glycol) succinate, poly(ethylene glycol) glutarate, poly(ethylene glycol) adipate, poly(ethylene glycol) pimelate, poly(ethylene glycol) suberate and the like.
8. The multi-layer co-extruded biaxially oriented film according to claim 1, Features: The thickness ratio of the PET layer of the A layer to the PP layer of the B layer is 1-10:1-10.
9. A method for preparing the multi-layer co-extruded biaxially oriented film according to claim 1, Features: Layer A and layer B are melt-extruded through a tandem screw extruder, and the two layers of raw materials are electrostatically attached to a cold drum to form a cast sheet through a co-extrusion die head equipped with a co-extrusion adapter; the thick sheet obtained after extrusion is sequentially stretched 3-5 times longitudinally and 6-8 times transversely, heat-set, relaxed, pulled, and rolled to form a multi-layer co-extruded biaxially stretched film with a thickness of 20-30μm.
10. Use of the multi-layer co-extruded biaxially oriented film according to claim 1 in food packaging.
Citation Information
Patent Citations
Coextrusion casting polyester film and preparation method thereof
CN102848676A
Multilayered co-extruded bidirectional-stretching light reflection polyester thin film and manufacturing method thereof
CN103753920A
Propylene-based polymer multi-layer composite film, and preparation method, use and product thereof
CN103847199A
Preparation method of multi-layer coextrusion bidirectionally-stretched composite thin film
CN107745509A
Thermochromic low-melting-point polyester film and preparation method thereof
CN111098577A
